The Influence of Work-Life Balance and Physical Work Environment on Employee Wellbeing of PT Arteria Daya Mulia Employees - Aulia Magfirani Putri; Siti Maryam (CV. AFDIFAL MAJU BERKAH, 2026)
Employee wellbeing is an important aspect of human resource management because it is closely related to employees' health, comfort, and sustainable job performance. This study aimed to examine the influence of work-life balance and the physical work environment on employee wellbeing at PT Arteria Daya Mulia. A quantitative research approach with a survey design was employed involving 68 employees selected through purposive sampling. Data were analyzed using multiple linear regression with SPSS, following validity, reliability, and classical assumption tests. The results revealed that Work-Life Balance had a positive and significant effect on Employee Wellbeing (B = 0.660, β = 0.425, t = 3.668, p < 0.001), while the Physical Work Environment also had a positive and significant effect (B = 0.293, β = 0.383, t = 3.309, p = 0.002). Simultaneously, both independent variables significantly influenced Employee Wellbeing (F = 40.468, p < 0.001) and explained 54.1% of its variance (Adjusted R² = 0.541). These findings indicate that maintaining a healthy work-life balance and providing a supportive physical work environment are essential strategies for enhancing employee wellbeing at PT Arteria Daya Mulia and may contribute to more sustainable organizational performance.